Challenges in implemeting ICT in teaching & learning in schools : a case study in Batu Pahat district / Azifa Abdullah, Nizati Mohamed and Shahrul Nizam Mohd Idris - Abdullah, Azifa; Mohamed, Nizati; Mohd Idris, Shahrul Nizam (2008)
The purpose of this study was to measure teacher's usage, attitude and perception towards information communication technology (ICT). The results revealed that most teachers possess positive attitudes towards JCT. The findings also established that most teachers have moderate levels of ICT competency. They also believe that they still lack the appropriate JCT skills to integrate the technology into the teaching and learning process. The result analysis indicated that there are insignificant difference between the group of teachers in terms of usefulness, attitude, perception and readiness in urban and rural area.